Analysis of the Relationship Between Interest in Continuing to College Based on Academic Achievement of Culinary Vocational High School Students - Adela Adela; Juliana Siregar; Elida Elida; Cici Andriani (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
The low participation of vocational high school graduates in higher education (10% nationally) is a challenge. This study examines the correlation between academic achievement and interest in continuing education among students at SMKN 1 Batusangkar. This quantitative correlational study involved 33 12th-grade students in the Culinary Services Expertise Program. Data were collected via a Google Form questionnaire (Likert scale 1-5, Cronbach's α = 0.85) and report card grades from the odd semester of 2023/2024. Analysis used Pearson Product-Moment correlation with SPSS. The results show a robust correlation between academic achievement and interest in continuing education (r = 0.99, p < 0.001). Students with high grades tend to be interested in college. Academic achievement can predict interest in continuing education with 99.6% accuracy. The findings encourage vocational high schools to prioritize improving academic achievement to boost interest in college, for example, through the implementation of mentoring programs.